2019
DOI: 10.1002/jcb.29161
|View full text |Cite
|
Sign up to set email alerts
|

The role of lncRNA RP11‐154D6 in steroid‐induced osteonecrosis of the femoral head through BMSC regulation

Abstract: Background Bone marrow stem cells (BMSCs) are involved in steroid‐induced osteonecrosis of the femoral head (ONFH). Long noncoding RNAs (lncRNAs) have been demonstrated to regulate functions of BMSCs, especially their differentiation, and have been reported to be implicated in diverse bone disorders. However, the roles of lncRNAs in the progression of steroid‐induced ONFH remain unknown. Methods BMSCs were isolated from healthy controls or patients with steroid‐induced ONFH. RNA‐sequencing was used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…For instance, the lncRNA TCONS_00041960 promotes osteogenic differentiation and suppresses adipogenic differentiation of GC-treated rat BM-MSCs, by directly sponging miR-204-5p and miR125a-3p [96]. In another study, the expression of the lncRNA RP11-154D6 was reduced in human BM-MSCs of patients with SONFH, and its overexpression enhanced osteogenic differentiation while inhibiting adipogenic differentiation [97]. However, more lncRNAs involved in osteogenesis and adipogenesis via GR need to be identified and studied.…”
Section: Transcription Factors and Post-transcriptional Regulators Inmentioning
confidence: 99%
“…For instance, the lncRNA TCONS_00041960 promotes osteogenic differentiation and suppresses adipogenic differentiation of GC-treated rat BM-MSCs, by directly sponging miR-204-5p and miR125a-3p [96]. In another study, the expression of the lncRNA RP11-154D6 was reduced in human BM-MSCs of patients with SONFH, and its overexpression enhanced osteogenic differentiation while inhibiting adipogenic differentiation [97]. However, more lncRNAs involved in osteogenesis and adipogenesis via GR need to be identified and studied.…”
Section: Transcription Factors and Post-transcriptional Regulators Inmentioning
confidence: 99%
“…It has been reported that lncRNAs act as the important regulators in SONFH through functioning as ceRNAs of miRNAs and target genes 12 . For example, lncRNA RP11-154D6 promotes osteogenic differentiation and inhibits adipogenic differentiation in bone marrow mesenchymal stem cells (BMSCs) to contribute SONFH progress 13 . lncRNA RP1-193H18.2, MALAT1, and HOTAIR were proved association with abnormal osteogenic and adipogenic differentiation of BMSCs in the patients with SONFH 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, a total of 1147 differentially expressed lncRNAs were identified in BMSCs isolated from patients with steroid-induced ONFH [5], including the confirmed downregulated expression of the lncRNA RP11-154D6 by qRT-PCR. In another study using steroid-induced ONFH mouse models, the lncRNA RP11-154D6 was shown to exert its function through interactions with miR-30a [24].…”
Section: Lncrna Expression Profiles In Bmscsmentioning
confidence: 99%
“…Although originally considered "noise" or "junk" RNAs, ncRNAs are now widely recognized as important regulators of gene expression, functioning at both transcriptional and posttranscriptional levels. Although the roles of ncRNAs in the development and progression of ONFH are gradually coming to light with progress in high-throughput sequencing techniques and associated analyses, there has been no comprehensive assessment of the related literature [5,6]. Accordingly, we here provide an overview on the role of ncRNAs in steroid-induced ONFH pathogenesis.…”
Section: Introductionmentioning
confidence: 99%